(untitled) (Revista de História Regional, 2007)
The objective of the present article is to discuss the penitentiary problem and how the press in Curitiba has presented it, during the first years of the Twentieth Century. Initially, there is an analysis of the speech used by the press to deal with criminality as a whole in the city. Then, this analysis is followed by an attempt to show how those considerations were the basis for the development of another speech, pointing to the necessity of an institution capable to provide the removal and imprisonment of the individuals deemed dangerous to society. More than the simple necessity for a penitentiary system though, lawmen of the period use the newspapers as a tribune to deliver a concept for the best model to be adopted regarding not so much as punish- ment but indeed physical and moral regeneration of the criminals. Throughout the text, the objective is also to per- ceive the similarity of views between what was thought in Curitiba and the frontline criminological thinking of the period.